Silicone Compositions Containing Acrylate Curing Accelerators
Patent Information
- Application Number
- JP2021577894
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-07-02
- Filing Date
- 2020-07-02
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2040-07-02
AI Technical Summary
【0033】 上記の一般的な記載および以下の詳細な説明の両方とも単なる例示にすぎず、特許請求の範囲の性質および特質を理解するための概要または枠組みを提供することが意図されることを理解されたい。添付の図面は、より良い理解を与えるために含まれており、本明細書に含まれ、本明細書の一部をなす。これらの図面は、1つ以上の実施形態を示しており、記載とともに、様々な実施形態の原理および動作を説明するのに役立つ。
Smart Images

Figure 0007641922000028 
Figure 0007641922000029 
Figure 0007641922000030
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a composition comprising a silicone-based polymer and an acrylate cure accelerator, which may be present at about 5% by weight or less based on the total weight of the composition. The acrylate cure accelerator (e.g., acrylate monomer) accelerates the rate and time of cure by beneficially lowering the peak cure temperature of the composition, and further reduces the amount of catalyst required to initiate effective cure, e.g., 90% or more. The present disclosure also relates to the addition of one or more O-vinyl compounds to silicone-containing compositions useful for adhesive liners and release products, where the acrylate cure accelerator and O-vinyl compound act synergistically to accelerate and improve completion of cure and reduce the peak cure temperature and the amount of catalyst required to initiate effective cure. The composition can be used as a material with desirable release properties, such as a release liner coating, silicone elastomer for medical devices, silicone elastomer for gaskets, and silicone elastomer for other molded articles. [Background technology]
[0002] Silicone resins are desirable for use in the adhesive industry because they provide elasticity and low surface energy. In particular, silicone-based compositions, such as coatings, can hold substrates (e.g., labels) in place for storage and transportation, and they also allow for easy and quick peeling of the substrate from the release liner. Traditional components of compositions used as coatings include silicones, crosslinking agents, and catalysts, including, for example, platinum catalysts. However, the high cost associated with the use of platinum catalysts has prompted the adhesive industry to investigate affordable alternatives. Little success has been achieved in reducing the amount of platinum catalyst required to successfully cure compositions containing silicones, at least because reducing the amount of platinum catalyst can lead to insufficient cure and / or slower cure rates. Summary of the Invention [Problem to be solved by the invention]
[0003] In view of the above, there is a need for a release coating composition that cures quickly without the large amounts of expensive platinum catalyst currently required to initiate and drive the cure of silicone compositions to completion. This specification describes compositions that can withstand the rigors of high temperature / high speed processing while also completing the cure quickly with reduced amounts of catalyst (e.g., platinum). This specification describes silicone-containing compositions that contain conventional amounts of catalyst but cure faster at temperatures significantly lower than currently known in the art. This specification also describes compositions that can be provided as a coating on a liner. The compositions can cure quickly to form a liner coating that holds the substrate (e.g., label) in place for storage and transportation, while also allowing the substrate to be easily and quickly peeled from the release liner. Furthermore, this specification also describes compositions that can be provided on a liner and introduced into adhesive articles such as label sheets. These compositions solve the problem of reducing the costs associated with the use of expensive catalysts and running high temperature ovens, while also promoting the cure of the composition without sacrificing the completeness of the cure, which can lead to poor bond quality or possible delamination between the composition and the adhesive on the substrate of the adhesive article. [Means for solving the problem]
[0004] In a first aspect, a composition is disclosed that includes a silicone-based polymer and a cure accelerator that is an acrylate monomer present in the composition in about 0.05 weight percent (wt%) to about 5 weight percent (wt%), based on the total weight of the composition.
[0005] In one example of embodiment 1, the silicone-based polymer is a vinyl-functional silicone-based polymer.
[0006] In another example of embodiment 1, the silicone-based polymer is present between about 50% and about 95% by weight of the total weight of the composition.
[0007] In another example of embodiment 1, the composition is uncured.
[0008] In another example of embodiment 1, the composition further comprises an O-vinyl ether compound, such as 1,4-cyclohexanedimethanol divinyl ether, butanediol divinyl ether (BDVE), and dodecyl vinyl ether (DDVE).
[0009] In another example of embodiment 1, the O-vinyl ether compound is present between about 0.01% and about 10% by weight of the total weight of the composition.
[0010] In another example of embodiment 1, the acrylate monomer is selected from the group of monofunctional, difunctional, trifunctional, or multifunctional acrylate monomers.
[0011] In another example of embodiment 1, the acrylate monomer is selected from the group of hexanediol diacrylate, tricyclodecanediol diacrylate, isobornyl acrylate, octyl / decyl acrylate, silicone diacrylate, silicone hexaacrylate, Tego RC722, 3-acryloxypropyltrimethoxysilane, and trimethylolpropane triacrylate.
[0012] In another example of embodiment 1, the acrylate monomer is present in an amount between about 0.05% and about 2% by weight of the total composition, or between about 0.05% and about 1% by weight of the total composition. In another example of embodiment 1, the acrylate monomer is present in an amount between about 0.1% and about 2% by weight of the total composition, or between about 0.1% and about 1% by weight of the total composition.
[0013] In another example of embodiment 1, the acrylate monomer is a hydrophilic acrylate monomer, for example, an acrylate monomer having a hydrophilic side chain or side group containing less than 12 carbons (C12).
[0014] In another example of embodiment 1, the composition further comprises a crosslinking agent having silicon hydride functional groups.
[0015] In another example of embodiment 1, the composition further comprises a controlled release agent (CRA).
[0016] In another example of embodiment 1, the controlled release agent is present in an amount less than about 50 wt.%, such as between about 4 wt.% and about 12 wt.%, of the total weight of the composition.
[0017] In another example of embodiment 1, the composition further comprises a catalyst, for example, a catalyst comprising platinum.
[0018] In another example of embodiment 1, the catalyst is present in a range between about 10 ppm and about 100 ppm, or up to 35 ppm, based on the total weight of the composition.
[0019] In a second embodiment, the composition of embodiment 1 is exposed to a temperature in the range of about 70° C. to about 140° C. for a period in the range of about 1 second to about 10 seconds, whereby the composition is 90% or more cured, for example, 95% or more cured. In another example, the composition of embodiment 1 is exposed to a temperature in the range of about 70° C. to about 140° C. for a period in the range of about 5 seconds to about 40 seconds, whereby the composition is 90% or more cured, for example, 95% or more cured.
[0020] In an example of embodiment 2, the period of time for which the composition is cured ranges from about 1 second to about 5 seconds, or less than 5 seconds. In another example, the period of time for which the composition is cured ranges from about 10 seconds to about 40 seconds, or less than 40 seconds.
[0021] In another example of embodiment 2, the temperature at which the composition is cured ranges from about 100°C to about 130°C.
[0022] In another example of embodiment 2, the elastic modulus (G') of the composition after curing is 1×10 measured at a temperature of about 120° C. 6 More than Pascal.
[0023] In another example of embodiment 2, the loss factor (tan δ) of the composition after curing is less than 0.01 measured at a temperature of about 120°C.
[0024] In another example of embodiment 2, the cured composition is a release material, such as a coating on a liner, an elastomer for a medical device, or an elastomer for a gasket.
[0025] In a third embodiment, there is a release liner comprising the cured composition of embodiment 1 and a liner having a first surface and a second surface, wherein the cured composition is disposed as a coating on a portion of the first surface of the liner.
[0026] In an example of embodiment 3, the liner is selected from the group of plastic or polymeric films, papers, and coated papers.
[0027] In a fourth aspect, there is an adhesive article that includes a substrate, an adhesive disposed on a surface of the substrate, and a release liner having a first surface and a second surface, wherein a portion of the first surface has the cured composition of aspect 1 disposed thereon and in contact with the adhesive.
[0028] In an example of embodiment 4, the substrate is a film, paper, or a combination thereof.
[0029] In another example of embodiment 4, the adhesive is a pressure sensitive adhesive.
[0030] In another example of embodiment 4, the liner is a plastic or polymeric film, paper, or coated paper.
[0031] Any one of the above aspects (or examples of those aspects) may be provided alone or in combination with any one or more examples of that aspect discussed above. For example, the first aspect may be provided alone or in combination with any one or more examples of the first aspect discussed above, and the second aspect may be provided alone or in combination with any one or more examples of the second aspect discussed above, etc.
[0032] Additional features and advantages will be set forth in the following detailed description, and in part will be readily apparent to those skilled in the art from that description, or will be learned by practice of the embodiments described herein, including the following detailed description, the claims, and the accompanying drawings.
[0033] It should be understood that both the foregoing general description and the following detailed description are merely exemplary and are intended to provide an overview or framework for understanding the nature and character of the claims. The accompanying drawings are included to provide a better understanding, and are incorporated into and constitute a part of this specification. The drawings illustrate one or more embodiments, and together with the description, serve to explain the principles and operation of the various embodiments. [Brief description of the drawings]
[0034] [Figure 1] FIG. 1 shows an exemplary relationship between the concentration of the acrylate monomer EOEOEA in parts per million (pph) and peak cure temperature (° C.) for silicone-based compositions containing 10 ppm, 20 ppm, and 30 parts per million (ppm) of platinum catalyst. [Diagram 2] FIG. 1 shows an exemplary relationship between the concentration of the acrylate monomer EOEOEA in parts per million (pph) and peak width in degrees Celsius (° C.) for silicone-based compositions containing 10 ppm, 20 ppm, and 30 ppm of platinum catalyst. [Diagram 3]FIG. 2 shows an exemplary relationship between the concentration of the acrylate monomer ODA in parts per million (pph) and the peak cure temperature in degrees Celsius (° C.) for a silicone-based composition containing 35 parts per million (ppm) of platinum catalyst. [Figure 4] FIG. 2 shows an exemplary relationship between the concentration of the acrylate monomer Tego RC722 in parts per million (pph) and the peak cure temperature in degrees Celsius (° C.) for a silicone-based composition containing 35 ppm platinum catalyst. [Diagram 5] FIG. 1 shows exemplary relationships between storage modulus in Pascals (Pa) and cure temperature in degrees Celsius (° C.) for a silicone-based composition without additives, a silicone-based composition containing an acrylate monomer (TMPTA), and a silicone-based composition containing an acrylate monomer / O-vinyl compound blend (TMPTA / BDVE). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0035] The terminology provided herein is merely illustrative of the embodiments and should not be construed as limiting the present invention as a whole. In the present specification, when a range such as 5-25 (or 5 to 25) is provided, this preferably means at least 5 or more than 5, and separately and independently preferably 25 or less than 25. In one example, such a range is defined as separately and independently 5 or more, and separately and independently 25 or less.
[0036] As used herein, the term "about" means that amounts, sizes, formulations, parameters, and other quantities and characteristics are not and need not be exact, but may be approximate and / or larger or smaller, if desired, to reflect tolerances, conversion factors, rounding, measurement errors, and other factors. When the term "about" is used in describing a value or an end point of a range, the present disclosure should be understood to include the specific value or end point referred to. Regardless of whether a numerical value or end point of a range is described as "about" herein, the numerical value or end point of the range is intended to include two embodiments (those modified by "about" and those not modified by "about"). It will be further understood that each end point of the range is valid both in relation to the other end point and independently of the other end point.
[0037] The terms "substantially", "substantially", and variations thereof, as used herein, are intended to note that the described feature is equal or approximately equal to the value or description. For example, a "substantially planar" surface is intended to indicate a surface that is planar or approximately planar. Furthermore, "substantially" is intended to indicate that two values are equal or approximately equal. In some embodiments, "substantially" may indicate values that are within about 10% of each other, such as within about 5% of each other, or within about 2% of each other.
[0038] It is noted that the terms "substantially" and "about" may be utilized herein to express the inherent degree of uncertainty that may result from any quantitative comparison, value, measurement, or other representation. These terms are also utilized herein to express the degree to which a quantitative representation may differ from the indicated reference without resulting in a change in the basic functionality of the subject matter at issue.
[0039] Provided is a composition that contains silicone and contains between about 0.05% and about 5% by weight or less of an acrylate cure accelerator (e.g., an acrylate monomer) based on the total weight of the composition. Adding one or more acrylate cure accelerators in these amounts to a composition that includes a silicone-based polymer, a catalyst, and a crosslinker desirably reduces the peak cure temperature of the composition, thereby accelerating the rate and time of cure. Surprisingly, it has also been found that adding an acrylate cure accelerator in these amounts selectively allows for a reduction in the amount of catalyst (e.g., a platinum-based catalyst) required to initiate and effectively complete the cure of the composition without sacrificing the completeness of the cure or detrimentally affecting the release properties of the cured silicone composition. The compositions provided herein are particularly useful in release liners, particularly for adhesive articles.
[0040] Materials of composition The curable composition of the present disclosure comprises one or more silicone-based polymers, so the composition is a silicone composition.The composition further comprises one or more acrylate monomers as curing accelerators, one or more catalysts, and one or more crosslinking agents.Optionally, in some embodiments, the composition can further comprise one or more O-vinyl compounds and control release agents as described herein.
[0041] Generally, one or more silicone-based polymers of the composition have reactive vinyl groups. In one or more embodiments, the silicone-based polymer is a vinyl-functional silicone-based polymer or siloxane, such as a diorganopolysiloxane or a dialkylpolysiloxane. In one example, the silicone-based polymer is a multifunctional polymer with vinyl groups along the polymer chain and / or at the end of the chain. In another example, the silicone-based polymer can be polydimethylsiloxane (PDMS) or a derivative thereof. Vinyl-terminated PDMS is an example of a silicone-based polymer. Exemplary silicone-based polymers used in the present disclosure include, but are not limited to, Wacker's Dehesive 915 and Dowsil SL 161. The total amount of silicone-based polymer (e.g., one or more silicone polymers) can be present in a range of about 50% to about 95% by weight, or about 60% to about 90% by weight, of the total weight of the composition. In another example, the composition contains about 50% by weight or more, about 60% by weight or more, about 65% by weight or more, about 70% by weight or more, or about 75% by weight or more total silicone-based polymer, based on the total weight of the composition, e.g., the uncured composition. In another example, the composition can contain about 95% by weight or less, about 90% by weight or less, about 85% by weight or less, or about 80% by weight or less total silicone-based polymer.
[0042] The acrylate curing accelerator, such as the acrylate monomer of the composition, functions to effectively and beneficially lower the peak curing temperature of the composition, thereby requiring a lower curing temperature and accelerating the rate and time of curing. The term "acrylate" used herein to define the acrylate curing accelerator specifically refers to acrylates and not to methacrylates or a combination of acrylates and methacrylates. In certain embodiments, the acrylate curing accelerator is hydrophilic and includes a hydrophilic side chain or side group containing less than 12 carbons (C12). The acrylate curing accelerator may be present in an amount between about 0.05% and about 5% by weight, based on the total weight of the composition. In another example, the acrylate curing accelerator is present in a range of about 0.1% to about 5% by weight, about 0.15% by weight or more, about 0.2% by weight or more, or about 0.25% by weight or more, based on the total weight of the composition. In another example, the composition may contain about 4.5 wt% or less, about 4 wt% or less, about 3.5 wt% or less, or about 3 wt% or less of acrylate cure accelerator. In one or more embodiments, the curable composition contains about 5 wt% or less of total acrylate cure accelerator to ensure the formation of a cured composition with a high modulus. In another example, the composition (e.g., in the uncured state) may contain acrylate cure accelerator in the range of about 0.1 pph to about 10 pph (parts of acrylate cure accelerator per 100 parts of silicone-based polymer present in the composition), about 0.2 pph to about 5 pph, about 0.25 pph to 5 pph, about 0.2 pph to about 2 pph, or about 0.5 pph, about 0.75 pph, about 1 pph, about 1.25 pph, about 1.5 pph, or about 1.75 pph. In another example, the composition may contain about 10 pph or less, about 5 pph or less, about 4 pph or less, about 3 pph or less, or about 2 pph or less of total acrylate cure accelerator. In yet another example, the composition may include up to about 0.1 pph, about 0.2 pph, about 0.25 pph, about 0.5 pph, about 1 pph, about 1.5 pph, about 2 pph, or about 5 pph of total acrylate cure accelerator.
[0043] In one or more embodiments, the one or more acrylate cure accelerators are acrylate monomers that are monofunctional acrylate monomers. In other embodiments, the one or more acrylate monomers are difunctional, trifunctional, or multifunctional. Exemplary acrylate monomers for use in the present invention include, but are not limited to, hexanediol diacrylate (HDDA), tricyclodecanediol diacrylate, isobornyl acrylate, octyl / decyl acrylate, silicone diacrylate, silicone hexaacrylate, Tego RC722, 3-acryloxypropyltrimethoxysilane, trimethylolpropane triacrylate (TMPTA), isodecyl acrylate (IDA), propoxylated (3 mol) TMPTA, ethoxylated (3 mol) TMPTA, 2-ethoxyethoxyethyl acrylate (EOEOEA), propoxylated 2-neopentyl glycol diacrylate (PONPGDA), 2-phenoxyethyl acrylate, ethoxylated (15 mol) TMPTA, polyethylene glycol 200 diacrylate (PEG200DA).
[0044] The compositions disclosed herein also contain a crosslinking agent or crosslinking agent, such as a silicon hydride agent. A wide variety of crosslinking agents, such as known polyorganohydrosiloxane crosslinking agents, can be used in the disclosed compositions. Crosslinking agents having silicon hydride functionality, i.e., Si-H groups, are particularly preferred. Exemplary crosslinking agents for use in the present invention include, but are not limited to, V90 available through Wacker Chemical, and Syl-Off 7488 available through Dow Chemical Corporation. The crosslinking agent can be present in a range between about 1% and about 15% by weight, based on the total weight of the composition. In another example, the crosslinking agent is present in a range of about 2% to about 14% by weight, about 3% or more, about 4% or more, or about 5% or more by weight, based on the total weight of the composition. In another example, the composition can contain about 14% or less, about 13% or less, or about 12% or less by weight of the crosslinking agent.
[0045] The composition disclosed herein also includes a catalyst, for example, a metal-based catalyst such as platinum or rhodium.Various catalysts can be used in the composition.Platinum (Pt)-containing catalysts, such as platinum, platinum complexes, or platinum compounds, are preferred for use in the composition.In one or more embodiments, the platinum catalyst is Karstedt's catalyst, which is an organoplatinum compound derived from divinyl-containing disiloxanes, suitable for hydrosilylation reactions.
[0046] The compositions often use more than 40 ppm of platinum catalyst. Less than 40 ppm of platinum catalyst can result in incomplete curing and insufficient bonding with the adhesive-coated substrate when the composition is used in a stripping application. However, in preferred embodiments of the compositions disclosed herein, the catalyst is present in an amount between about 5 ppm and about 100 ppm, about 10 ppm and about 80 ppm, or about 15 ppm and about 60 ppm of the total weight of the composition. In some embodiments, the catalyst (e.g., platinum-based catalyst) comprises about 40 ppm or less, about 35 ppm or less, about 30 ppm or less, about 25 ppm or less, or about 20 ppm or less of the total weight of the composition. In one or more embodiments, the amount of platinum catalyst can be in the range of about 1 ppm to about 20 ppm of the total weight of the composition. In other embodiments, the amount of platinum catalyst can be in the range of about 5 ppm to about 10 ppm of the total weight of the composition.
[0047] In one or more embodiments of the composition, the composition also optionally includes an O-vinyl compound. A wide variety of O-vinyl compounds may be used in the composition. For example, O-vinyl ether compounds may be used. In one or more embodiments, the O-vinyl ether compound is selected from 1,4-cyclohexanedimethanol divinyl ether, butanediol divinyl ether (BDVE), and dodecyl vinyl ether (DDVE). The O-vinyl compound may be present in a range of about 0.01% or 0.05% to about 5% or less by weight, or about 0.1% to about 3% by weight, based on the total weight of the composition. In one or more embodiments, the O-vinyl compound is present in about 2.5% or less by weight, about 2% or less by weight, about 1% or less by weight, or about 0.5% or less by weight of the total weight of the composition.
[0048] In another embodiment of the composition, the composition also includes a controlled release agent (CRA). The controlled release agent, when added to the composition, functions to adjust the bond strength of the composition, for example, when used as an adhesive article. In one or more embodiments, the controlled release agent includes a monovalent (M) siloxane group (RSiO 1 / 2 groups, where R is a monovalent hydrocarbon group, typically methyl or vinyl, and tetravalent (Q) siloxane groups (SiO 4 / 2 Silicone resins, also known as MQ resins, include silicone resins that contain only vinyl groups. The vinyl groups allow the CRA to react with the silicone polymer during curing. In one or more embodiments, the controlled release agent can be CRA 17 available from Wacker, or SL 40 supplied by Dow Chemical. The controlled release agent can be present in an amount of less than 50% by weight of the total weight of the composition. In other embodiments, the controlled release agent can be present in a range between about 1% to about 35% by weight, about 2% to about 25% by weight, or about 4% to about 12% by weight, based on the total weight of the composition.
[0049] Exemplary compositions according to the present disclosure are shown in Table 1 below: [Table 1]
[0050] Preparation of the Composition The following is an exemplary method of preparing the composition. The silicone-based polymer, the crosslinking agent, the catalyst, and optionally the controlled release agent are added together, and the components are mixed together, for example, for about 5 minutes to about 25 minutes or until completely mixed, to prepare a mixture. The acrylate cure accelerator, and optionally the O-vinyl ether compound, are added to the mixture, and further mixed (for example, for about 5 minutes to about 25 minutes) to form a reactive mixture. In one or more embodiments, the step of adding the acrylate cure accelerator, and optionally the O-vinyl ether compound, to the components of the mixture in the method of preparing a curable (e.g., thermosetting) composition is performed immediately before applying the curing conditions, for example, immediately before heating the composition.
[0051] In one or more embodiments, the silicone base polymer and the crosslinker are combined together and mixed until a uniform blend is achieved, after which an optional controlled release agent can be added. The blend is further mixed or stirred until uniform. A catalyst is further added, for example in the form of a solution, such as a platinum-containing solution, and mixed to form a mixture. An acrylate cure accelerator, and optionally an O-vinyl ether compound, are added to the mixture and further mixed (e.g., for about 5 minutes to about 25 minutes) to form a reactive mixture. The reactive mixture is subjected to curing conditions, for example, heating the composition. Heating can be achieved by any suitable means, for example, in an oven.
[0052] Curing conditions for the composition may include exposing the composition to heat. In one example, the composition is heated in an oven or series of ovens to initiate curing. The ovens may be preheated to a range of about 130°C to about 150°C to carry out the curing. However, it has been found that the compositions disclosed herein may be cured to about 90% or more, or about 95% or more, when the compositions are heated to a range of about 70°C to about 140°C, about 75°C to about 130°C, or about 80°C to about 120°C. In one or more embodiments, the coating composition may be cured to about 90% or more, or about 95% or more, when the compositions are heated to a range of about 70°C to about 120°C, about 75°C to about 115°C, or about 80°C to about 110°C. In other embodiments, the composition may be cured at higher temperatures, for example, in the range of about 120°C to about 180°C, about 125°C to about 170°C, or about 130°C to about 160°C, or at about 140°C or 150°C, to about 90% or more, or about 95% or more.
[0053] As supported by the following examples, the use of an acrylate curing accelerator can reduce the peak curing temperature of the composition, for example, in the range of about 70°C to about 140°C, about 75°C to about 135°C, about 80°C to about 130°C, or about 90°C, about 100°C, about 110°C, or about 120°C. Curing conditions, such as exposure temperature, for the composition can be adjusted accordingly. For example, oven temperature can be set lower than typical curing temperature with the use of an acrylate curing accelerator. Also, in the examples, the curing temperature to achieve 95% or more cure is shown to be in the range of about 70°C to about 140°C, about 75°C to about 135°C, about 80°C to about 130°C, or about 90°C, about 100°C, about 110°C, or about 120°C.
[0054] The composition also benefits from the use of an acrylate cure accelerator in that the amount of time to achieve effective (e.g., 90% or 95% or more) cure is reduced, e.g., residence time in a heated condition such as an oven. In one or more embodiments, the composition may be cured at a temperature ranging from about 70°C to about 130°C, about 75°C to about 125°C, or about 80°C to about 120°C for a period of about 1 second to about 1 minute, about 2 seconds to about 45 seconds, about 3 seconds to about 30 seconds, about 25 seconds or less, about 20 seconds or less, about 15 seconds or less, about 10 seconds or less, about 8 seconds or less, or about 5 seconds or less. In other embodiments, higher cure temperatures, e.g., in the range of about 120°C to about 180°C, about 125°C to about 170°C, or about 130°C to about 160°C, or about 140°C or 150°C, may be used with the same cure times as above. The curing time for curing the composition may range from 10 seconds to 40 seconds or more, in the example where the composition should be cured and the adhesive material of the adhesive article described herein should be dried at the same time. In one or more embodiments, the composition may be applied as an uncured coating on the first surface of the liner substrate of the release liner. The release liner with the composition coating may be disposed on a substrate (e.g., a label that may be made of a polymer film, paper, or a combination thereof) that is at least partially covered with a thin layer of adhesive that may be pressure sensitive. The composition coating of the release liner may be in direct contact with the adhesive on the substrate, so that the adhesive layer is disposed between the substrate and the coating composition on the liner material of the release liner. The article may be heated in an oven under the above conditions to cure the composition of the release liner and dry the adhesive on the substrate, for example, by exposing the article to a temperature in the range of about 70°C to about 130°C, about 75°C to about 125°C, or about 80°C to about 120°C for a period of about 10 seconds to about 40 seconds or 1 minute.
[0055] Release Liner The present disclosure also provides the use of the application of the composition to coat a flexible liner that can be used to form a release liner. The release liner functions as a carrier for and protects the substrate (e.g., label). The composition disclosed herein is typically applied to the surface of the flexible liner as a very thin release layer or coating (e.g., about 1 μm, microns). The thickness of the release layer of the composition can range from about 0.05 μm to about 3 μm, about 0.1 μm to about 2 μm, about 0.25 μm to about 1 μm, or about 0.5 μm, about 0.75 μm, about 1 μm, about 1.5 μm, or about 2 μm. The application of the release layer of the composition to the surface of the liner provides a resilient, low energy layer that holds the label in place on the surface of the liner during storage, while also providing quick and easy removal.
[0056] In some embodiments, the flexible liner coated with the composition can be a polymer film, a paper material, and / or a coated paper material. A variety of materials can be used for the flexible liner, including but not limited to conventional smooth surface paper material, polyester film, and polyolefin film. In certain embodiments, the flexible liner coated with the composition (i.e., the release liner) is thick enough to reinforce the backing sheet. In a preferred embodiment, the release liner has sufficient rigidity and / or thickness to maintain a flat configuration, while at the same time being flexible enough to bend in response to external stimuli.
[0057] To prevent the silicone polymer from migrating into the adhesive and interfering with the adhesion of adhesive articles such as labels, the composition coated onto the flexible liner must be crosslinked by a process known as curing. Uncured silicone in the composition is undesirable as it can interfere with printing and other label processing steps.
[0058] Once the composition for coating the flexible liner is prepared as disclosed above, the composition is applied to the flexible liner using a series of rollers. The rollers grind the composition and form the reactive mixture into a thin layer of the thickness on the flexible liner. The coated release liner is then heated, for example in an oven or series of ovens, to initiate curing of the reactive mixture. Typically, the oven is heated to a temperature in the range of about 130°C to about 150°C to effect the curing. However, it has been found that the release liner coating composition disclosed herein can be cured to about 90% or more, or about 95% or more, when the oven is heated to a temperature less than 130°C, for example, in the range of about 70°C to about 130°C, about 75°C to about 125°C, or about 80°C to about 120°C. In one or more embodiments, the composition coated on the flexible liner may be about 90% or more cured, or about 95% or more cured, when the composition is heated to a temperature range of about 70°C to about 120°C, about 75°C to about 115°C, or about 80°C to about 110°C.
[0059] In one example, the coated flexible liner is passed through an oven at approximately 2000 feet per minute such that the time of exposure to the elevated temperature during which curing occurs is between about 1 second and about 5 or 10 seconds. In some embodiments, the time during which curing occurs ranges from 1 second to 5 seconds, or about 2, 3, or 4 seconds. During curing, the vinyl groups of the silicone react with the silicon hydride groups of the crosslinking agent through a process called hydrosilylation. The resulting product is a highly crosslinked three-dimensional polymer. No volatile by-products are produced during the curing process. Once the liner exits the oven and returns to room temperature, little or no post-curing occurs. In one or more embodiments, the composition may be cured at temperatures ranging from about 70° C. to about 140° C., about 75° C. to about 130° C., or about 80° C. to about 120° C. for periods of about 1 second to about 30 seconds, about 2 seconds to about 25 seconds, about 20 seconds or less, about 15 seconds or less, about 10 seconds or less, or about 5 seconds or less.
[0060] The hydrosilylation that occurs during silicone cure is an exothermic process that produces an exothermic peak that is measured using Differential Scanning Calorimetry (DSC). DSC is an industry-accepted method that analyzes the difference in the amount of heat required to increase the temperature of a sample compared to a reference, measured as a function of temperature. Typically, the temperature is increased at 10°C per minute. Heat flow is typically measured in watts.
[0061] Several measurements of the exotherm peak provide information about the overall cure. The peak temperature, typically measured in degrees Celsius (°C), is the temperature at which the exotherm peak reaches its maximum. The peak area, typically measured in Joules per gram (J / g), is a measure of the total heat release and is a measure of the completeness of the cure. A higher peak area generally indicates a greater completeness of the cure. The peak width, typically measured in degrees Celsius (°C), is a measure of the rate at which the cure occurs. The peak height, typically measured in watts per gram (W / g), indicates the extent (strength) of the cure. A narrow, high exotherm peak indicates a fast, intense cure, whereas a short, broad exotherm peak indicates a slow, gradual cure of the silicone composition. The temperature at which the silicone polymer is 95% cured is also typically measured in degrees Celsius (°C).
[0062] Unlike DSC results, a rheometer can reveal the physical properties of a material as the temperature increases during curing. Typically, the elastic shear modulus (G') is measured. The first derivative of the modulus indicates how rapidly the reaction is increasing. The temperature at which the first derivative is maximum is a measure of the maximum reaction rate, which is roughly equivalent to the peak cure temperature obtained via DSC. The maximum value of the first derivative, typically measured in Pascals per degree Celsius (Pa / °C), indicates the maximum crosslinking rate, and the temperature of the maximum indicates the temperature at which the maximum rate occurs. The second derivative of the elastic curve indicates how the reaction rate is changing. The minimum temperature of the second derivative, typically measured in degrees Celsius (°C), is the temperature at which curing is nearly complete. The G' at the minimum temperature of the second derivative, measured in Pascals (Pa), indicates the point at which the reaction has slowed to near completion.
[0063] adhesive article The present disclosure also provides an adhesive article comprising a substrate, an adhesive applied on the substrate, and a release liner with a cured composition layered on the surface. The composition can be applied as a solution onto the substrate or liner material forming the release liner, and then the coated solution is cured by applying heat as disclosed above to complete the formation of the release liner. The present disclosure includes examples of methods for providing the composition as a release layer onto the base material (e.g., paper liner) of the release liner, such as various conventional methods, for example, gravure coating, bar coating, spray coating, spin coating, knife coating, roll coating, die coating, etc. In some embodiments, the substrate is a label that can be made of polymer film, paper, or a combination thereof. The substrate is at least partially covered with a thin layer of adhesive, which can be pressure sensitive. The adhesive layer is disposed between the substrate and the cured release layer of the composition.
[0064] The adhesive layer may be formed from any suitable adhesive material desired for a particular purpose or intended application. The adhesive layer may include a pressure-sensitive adhesive layer, or a heat-activated adhesive layer. The pressure-sensitive adhesive may be any pressure-sensitive adhesive currently known in the art, such as acrylic adhesives, vinyl ether adhesives, polyester adhesives, polyurethane adhesives, rubber adhesives, silicone adhesives, and the like, or any combination thereof. In other examples, the adhesive may be either emulsion-type, solvent-type, and non-solvent-type, and may be either crosslinked or non-crosslinked. Useful pressure-sensitive adhesive materials may contain adhesive polymers, including, as a major component, for example, acrylic-type polymers, block copolymers, natural rubber, reclaimed rubber or styrene butadiene rubber, tacky natural or synthetic rubber, random copolymers of ethylene and vinyl acetate, ethylene-vinyl-acrylic terpolymers, and polyisobutylene, poly(vinyl ether). Typically, pressure-sensitive adhesive materials are typically characterized by a glass transition temperature in the range of about -70°C to about 10°C.
[0065] In addition to the above, additional components can be incorporated into the pressure-sensitive adhesive material. These additional components include, for example, solid adhesive resins, liquid tackifiers (e.g., plasticizers), antioxidants, fillers, pigments, waxes, etc., or blends thereof. Particularly useful adhesives are described in U.S. Pat. Nos. 5,192,612 and 5,346,766.
[0066] The adhesive layer may have a thickness desired for a particular purpose or intended use. In one embodiment, the adhesive layer may have a thickness of from about 10 microns to about 125 microns, or from about 10 microns to about 75 microns, or from about 10 microns to about 50 microns. In one embodiment, the coat weight of the pressure sensitive adhesive may range from about 10 grams per square meter (gsm) to about 50 gsm, and in one embodiment, from about 20 gsm to about 35 gsm.
[0067] The assembly of the adhesive layer is not limited and may be any suitable assembly or configuration required for a particular purpose or intended use. In one embodiment, for example, the adhesive layer may include a single layer, two layers, or multiple layers. In one embodiment, the adhesive layer(s) may also be substantially continuous. In another embodiment, the adhesive layer(s) may be provided as one or more discontinuous layers.
[0068] It will be apparent to those skilled in the art that various modifications and variations can be made to the disclosed embodiments without departing from the spirit and scope of the disclosure, and therefore, the disclosure is intended to cover any and all such modifications and variations that come within the scope of the appended claims and their equivalents. EXAMPLES
[0069] To demonstrate the effect of certain additives on the compositions, cure studies were conducted using compositions prepared according to Table 2.
[0070] [Table 2]
[0071] Silicone base polymer Dehesive 915 (DEH 915) is a short chain linear difunctional vinyl terminated silicone polymer provided by Wacker Chemicals and was used in the silicone base polymer. CRA 17, a silicone release improver resin (e.g., controlled release agent), was added to demonstrate compatibility between the additive being tested and other components in the release coating composition. V90, a silicone crosslinker provided by Wacker Chemical, and 20 ppm HSPC (20 ppm platinum atomic weight), a platinum catalyst diluted in the silicone polymer, were also added to the silicone base composition.
[0072] 1 pph of various additives including acrylate cure accelerators and O-vinyl compounds as shown in Table 3 below were added to the composition mixtures identified in Table 2 to form reactive mixtures for curing. The reactive compositions were cured in the DSC at a ramp of 10° C. / min as described above, and the peak temperature, peak height, peak width, peak area, and temperature at 95% cure of the release coating compositions were measured via DSC as described above. The results obtained are also included in Table 3.
[0073] [Table 3]
[0074] From Table 3, it can be readily observed that the peak cure temperature for the acrylate monomer-containing composition was reduced by approximately 7 degrees Celsius to 15 degrees Celsius compared to the additive-free control composition. Also, the peak cure temperature was reduced more for the acrylate monomer-containing composition than for the other compounds tested. Since the peak temperature was reduced significantly for the acrylate monomer-containing composition, it can be concluded that the acrylate monomer, along with the presence of a small amount of catalyst (20 ppm), contributed directly to the cure acceleration. In contrast, it is also observed in Table 3 that N-vinyl compounds, vinyl compounds, and methacrylates did not beneficially change the peak cure temperature and, in some cases, even increased the cure temperature.
[0075] Additionally, broader and shorter exothermic peak heights were observed for the acrylate monomer-containing compositions compared to the additive-free control compositions. The slightly broader and shorter peaks indicated that the acrylates lowered the peak cure temperature, but slowed the cure slightly at the reduced temperature. However, the O-vinyl ethers did not lower the peak cure temperature, but did increase the reaction rate, as indicated by the higher peak heights while maintaining a narrow peak area.
[0076] To investigate the effect of additives on compositions with higher concentrations of platinum catalyst, the experiment presented in Table 3 was reproduced using a composition according to Table 4. This composition used the same ingredients as in Table 2. However, the amount of vinyl terminated base polymer was reduced and the amount of platinum was increased to 60 ppm. The amounts of silicone crosslinker and release improver resin were kept approximately the same.
[0077] [Table 4]
[0078] For this study, smaller amounts of additives were added to the composition. Specifically, 0.5 pph of various types of additives, including acrylate monomers and O-vinyl compounds, as shown in Table 5 below, were added to the composition to form a reactive mixture. The composition was cured, and the peak temperature, peak height, peak width, peak area, and temperature at 95% cure of the composition were measured via DSC as described above. The results are listed in Table 5.
[0079] [Table 5]
[0080] From Table 5, it can be readily observed that the acrylate monomer-containing compositions exhibited a significant reduction in peak cure temperature (e.g., approximately 8.4 degrees Celsius to 22.9 degrees Celsius lower) compared to the additive-free control composition. Compared to the 20 ppm platinum-catalyzed acrylate-containing compositions studied in Table 3, the 60 ppm platinum-catalyzed acrylate monomer-containing compositions exhibited an even more dramatic increase in peak cure temperature. Similarly, it can be seen that the O-vinyl compounds only reduced the peak cure temperature by 0.9 degrees Celsius to 2.7 degrees Celsius, but they increased the peak height while maintaining a narrow peak width. Thus, the O-vinyl compounds enhance the strength of the cure. Thus, it can be seen that the acrylates and O-vinyl ethers affect cure in an independent but complementary manner.
[0081] In terms of peak area, the acrylate-containing compositions generally exhibited greater peak area values than the additive-free control composition, although the extent varied depending on the type of acrylate monomer used. Similarly, the O-vinyl compounds tested consistently exhibited greater peak areas and peak heights than both the acrylate-monomer-containing compositions and the additive-free control compositions. Thus, it can be concluded that the inclusion of acrylate monomers and O-vinyl compounds can cause a greater portion of the composition to cure (e.g., increased cure). Nevertheless, the results in Tables 3 and 5 show that the acceleration and increase in cure caused by acrylate monomers and O-vinyl compounds occurred over a range of platinum catalyst concentrations (20 ppm to 60 ppm) and additive amounts (0.5 pph to 1 pph). Thus, small amounts of cure accelerator and small amounts of catalyst can be utilized while still achieving effective cure.
[0082] To demonstrate that cure acceleration and cure enhancement is not limited to the components of the silicone-based composition used in the previous study, the experiments were repeated using compositions containing various silicone polymers, crosslinkers, and controlled release agents as listed in Table 6. Additionally, the compositions contained a small amount of catalyst (35 ppm platinum catalyst) as opposed to the 20 ppm and 60 ppm concentrations tested in the previous study.
[0083] [Table 6]
[0084] SL 161 provided by Dow Chemical, a vinyl-terminated multifunctional silicone polymer containing vinyl groups along the polymer chain, was used in the silicone base polymer. SL 40, a silicone release improver resin (e.g., controlled release agent), was added to demonstrate compatibility between the tested additive and other components in the release coating composition. 7488, a silicone crosslinker provided by Wacker Chemical, and 35 ppm of SL 3000, a platinum catalyst, were also added to the silicone base composition.
[0085] 0.5 pph of various additives was added to the silicone-based composition as described in Table 7. The compositions were cured and the peak temperature, peak height, peak width, peak area, and temperature at 95% cure of the compositions were measured via DSC as described above. The results are included in Table 7.
[0086] [Table 7]
[0087] From Table 7, it is clear that the acrylate-containing compositions exhibited significantly lower peak cure temperatures compared to the control compositions without additives. The O-vinyl compounds did not significantly affect the peak cure temperatures. Therefore, it can be concluded that the ability of the acrylate monomers to accelerate cure is independent of the specific type of silicone polymer, crosslinker, controlled release agent, and platinum catalyst used in the silicone-based coating composition. Comparing the results of Tables 3, 5, and 7, it can be further concluded that the acrylate monomers accelerate cure independently of the amount of platinum catalyst present in the silicone-based composition.
[0088] In contrast to the control composition without additives, shorter and broader peaks were observed in the acrylate monomer-containing composition. Both the acrylate monomer-containing composition and the O-vinyl compound-containing composition showed increased peak areas when compared to the control composition without additives, indicating that more of these silicone-based compositions were cured (e.g., curing was enhanced). However, the O-vinyl compound, which generally has a larger peak height, proved to be the most effective curing accelerator. Considering these results, it is clear that the curing enhancement properties of the O-vinyl compound and the acrylate monomer are independent of the specific amount and type of silicone polymer, crosslinker, control release agent, and platinum catalyst used in the silicone-based coating composition.
[0089] To further demonstrate the cure accelerating and cure enhancing capabilities of acrylate monomers across silicone compositions containing various levels of platinum catalyst, silicone base compositions according to Table 8 were prepared. SL 161 was used as the silicone base polymer and 7488 was used as the silicone crosslinker. No controlled release agent was added to these compositions. SL 3000, a platinum catalyst, was added to the compositions in amounts of 10 ppm, 20 ppm, 30 ppm, and 35 ppm, respectively, as shown below.
[0090] [Table 8]
[0091] The acrylate monomer 2-ethoxyethoxyethyl acrylate (EOEOEA) was used as an additive and was added in amounts of 0.25 pph, 0.5 pph, 1 pph, 2 pph, 5 pph, and 10 pph in addition to 10 ppm, 20 ppm, and 30 ppm of the silicone base composition, respectively. Once EOEOEA was added, the composition was cured and the peak temperature, peak height, peak width, peak area, and temperature at 95% cure were measured via DSC as described above. The results are shown below in Table 9.
[0092] [Table 9]
[0093] As can be seen from Table 9, the EOEOEA-containing compositions at each platinum concentration exhibited a substantial reduction in peak cure temperature and caused accelerated cure. Perhaps more importantly, the amount of acrylate monomer required to achieve the most significant cure acceleration can be determined from Table 9. As shown in FIG. 1, the most rapid reduction in peak cure temperature occurred when between about 0.25 pph and about 2 pph of EOEOEA was added to the base composition across a range of platinum-containing concentrations. The addition of an amount of acrylate monomer greater than about 2 pph also caused a reduction in peak temperature, but the reduction was less significant. Therefore, regardless of the platinum concentration of the composition as supported by the examples, it can be concluded that the most significant cure acceleration is observed when about 2 pph or less of acrylate monomer is added to the silicone base composition prior to curing.
[0094] Similarly, as shown in Figure 2, when between about 0.25 pph and about 2 pph of EOEOEA was added to the various platinum-containing compositions, the peak width increased dramatically. However, when between about 2 pph and about 10 pph of EOEOEA was added to the compositions, the change in peak width remained nearly constant. Thus, Figure 2 also shows that the most significant cure acceleration occurs when about 2 pph or less of acrylate monomer is added to the silicone-based composition, regardless of the platinum concentration of the composition.
[0095] To demonstrate that acrylate monomers at about 2 pph or less cause the most significant cure acceleration across a range of acrylate monomer and platinum catalyst concentrations, additional acrylate monomers were studied in various amounts in silicone-based compositions containing higher concentrations of platinum catalyst. Two acrylate monomers, octyl / decyl acrylate (ODA) and Tego RC722-silicone acrylate fixative (Tego RC722), were added to the silicone-based composition at 35 ppm as shown in Table 8 above. The acrylate monomers were added to the silicone-based composition in amounts of 0.1 pph, 0.2 pph, 0.5 pph, 1 pph, 2 pph, 5 pph, and 10 pph, respectively. Once the acrylate monomers were added, the compositions were cured as described above, and the peak temperature, peak height, peak width, peak area, and temperature at 95% cure were measured via DSC. The results are shown in Tables 10 and 11 below, respectively.
[0096] [Table 10]
[0097] [Table 11]
[0098] As evidenced by the reduction in peak cure temperature shown in Tables 10 and 11, the acrylate-containing compositions exhibited accelerated cure (e.g., reduced peak temperature) when compared to the acrylate-free control compositions. The peak cure temperatures in Tables 10 and 11 were plotted against the amount of acrylate to produce Figures 3 and 4, respectively. Both Figures 3 and 4 show, for example, a sharp reduction in peak cure temperature for compositions containing ODA and Tego RC722 in an amount of about 2 pph or less when the acrylate cure accelerator was added in an amount of about 0.2 pph to about 2 pph or about 0.2 wt % to about 2 wt %. Adding more than about 2 pph of the acrylate cure accelerator did not reduce the temperature as dramatically, but was still effective. Thus, it can be concluded that the addition of about 2 pph or less (e.g., about 0.1 pph or about 0.2 pph to about 2 pph) of acrylate monomer as a cure accelerator to a silicone-based composition results in a significant reduction in the peak cure temperature, and that this range is generally most effective for all acrylate monomers, regardless of the platinum concentration of the composition, which may be about 60 ppm or less, about 50 ppm or less, about 40 ppm or less, or about 35 ppm or less.
[0099] The above studies focused on the addition of a single type of additive to the silicone base composition. Thus, a study was conducted by adding two additives to the silicone base composition, namely, one acrylate monomer and one O-vinyl compound. Silicone base compositions of 10 ppm, 20 ppm, and 30 ppm shown in Table 8 above were used in this study. One acrylate monomer (TMPTA) and one O-vinyl compound (BDVE) were added to the silicone base composition in the amounts shown in Table 12. Once TMPTA and BDVE were added, the composition was cured and the peak temperature, peak height, peak width, peak area, and temperature at 95% cure were measured via DSC as described above. The results are shown in Table 12.
[0100] [Table 12]
[0101] Table 12 shows that the combination of acrylate monomer (TMPTA) and O-vinyl compound (BDVE) results in a significant reduction in peak cure temperature when compared to the additive-free control composition, the acrylate monomer-containing composition, and the O-vinyl compound-containing composition. Since the composition containing the acrylate monomer / O-vinyl compound blend reduced the peak cure temperature the most, it can be concluded that the acrylate monomer / O-vinyl compound blend is an effective cure accelerator combination.
[0102] Similarly, compositions containing both acrylate monomers and O-vinyl compounds exhibited the largest peak areas while maintaining peak height and reaction rate, indicating that they were more partially cured (e.g., cured more) than the additive-free compositions, the acrylate monomer-containing compositions, and the O-vinyl compound-containing compositions. It can therefore be concluded that acrylate monomer / O-vinyl compound blends are also effective cure accelerators.
[0103] To evaluate the potential effect of acrylate monomers on the elasticity of the cured silicone base composition, a study was conducted via rheometer using a silicone base composition containing 10 ppm of platinum catalyst as shown in Table 8 above. 0.25 pph of additive was added to the base composition as shown in Table 13 below. Once the additive was introduced, the composition was cured as described above and the rheometer was used to obtain the maximum temperature of the first derivative, the maximum reaction rate of the first derivative, the minimum temperature of the second derivative, and the G' at the minimum temperature value of the second derivative. The results are shown in Table 13 below.
[0104] [Table 13]
[0105] As evidenced by the G' at the lowest temperature value of the second derivative for the acrylate monomer-containing compositions and the acrylate-free control composition in Table 13, the acrylate monomers generally do not appear to have a significant effect on the elasticity of the cured compositions.
[0106] Finally, to evaluate the effect of acrylate and O-vinyl compounds on the elasticity of the cured compositions, cure studies were performed via rheometer on a silicone base composition containing no additive (control), a silicone base composition containing only acrylate monomers, and a silicone base composition containing a blend of acrylate monomers and O-vinyl. 0.25 pph of the acrylate monomer TMPTA was added to 30 ppm of the platinum catalyzed silicone base composition shown in Table 8. Similarly, 0.25 pph of TMPTA and 0.2 pph of o-vinyl ether BDVE were added to another 30 ppm of the platinum catalyzed silicone base composition shown in Table 8. These two samples were added to one sample containing no additive (control) and subjected to cure as described above. Storage modulus values were measured via rheometer as the temperature was continuously increased at 10° C. / min. The data obtained are shown in Table 14 below and in FIG. 5.
[0107] [Table 14]
[0108] As shown in FIG. 5, the compositions containing only TMPTA and the compositions containing TMPTA / BDVE achieved peak cure temperatures approximately 10 degrees Celsius and 13 degrees Celsius lower than the additive-free compositions, respectively. This indicates that the compositions containing only TMPTA and the compositions containing TMPTA / BDVE exhibit accelerated cure rates, with the compositions containing TMPTA / BDVE curing slightly faster. Furthermore, the compositions containing only TMPTA and the compositions containing TMPTA / BDVE also achieved higher storage modulus values than the additive-free compositions, with the compositions containing TMPTA / BDVE exhibiting the highest storage modulus values. This confirms that the use of acrylate monomers, O-vinyl compounds, or blends thereof does not adversely affect the elasticity of the cured silicone-based compositions.
[0109] To demonstrate the application of the composition of the present disclosure onto a flexible liner to form a release liner, in addition to forming an adhesive article, compositions were formed from the following components listed in Tables 15-19.
[0110] [Table 15]
[0111] Dehesive 915 (DEH 915), a silicone base polymer, is a short-chain, linear, difunctional vinyl-terminated silicone polymer provided by Wacker Chemicals and was used for the silicone base polymer. V90, a silicone crosslinker provided by Wacker Chemical, was added and mixed until uniform. The silicone crosslinker is an organohydrogenpolysiloxane with an average of at least two silicon-bonded hydrogen atoms (Si-H groups) per molecule in an amount equal to 1 to 5 times the moles of alkenyl groups in the silicone base polymer. CRA 17, a silicone release improver resin (e.g., controlled release agent), was added to the silicone base polymer and mixed until uniform. Wacker HSPC, a platinum solution, was used to provide a ppm of platinum of 30 ppm by atomic weight of platinum. Finally, 0.2 parts by weight of 3-acryloxypropyltrimethoxysilane, an acrylate cure accelerator, was added to the mixture and mixed for 10 minutes.
[0112] The first control composition combined the ingredients listed in Table 16.
[0113] [Table 16]
[0114] Silicone base polymer, Dehesive 915 (DEH 915), a short chain, linear, difunctional vinyl terminated silicone polymer provided by Wacker Chemicals, was used for the silicone base polymer. Silicone crosslinker, V90, provided by Wacker Chemical, was added and mixed until uniform. Silicone release improver resin (e.g., controlled release agent), CRA 17, was added to the silicone base polymer and mixed until uniform. Platinum solution, Wacker HSPC, was used to bring the ppm of platinum to 60 ppm by atomic weight of platinum. Finally, 0.5 parts by weight of vinyltrimethoxysilane was added to the mixture as a cure accelerator and mixed for 10 minutes.
[0115] A second control composition combined the ingredients listed in Table 17.
[0116] [Table 17]
[0117] Silicone base polymer, Dehesive 915 (DEH 915), a short chain, linear, difunctional vinyl terminated silicone polymer provided by Wacker Chemicals, was used for the silicone base polymer. Silicone crosslinker, V90, provided by Wacker Chemical, was added and mixed until uniform. Silicone release improver resin (e.g., controlled release agent), CRA 17, was added to the silicone base polymer and mixed until uniform. Platinum solution, Wacker HSPC, was used to bring the ppm of platinum to 15 ppm by atomic weight of platinum. Finally, 0.5 parts by weight of vinyltrimethoxysilane was added to the mixture as a cure accelerator and mixed for 10 minutes.
[0118] Another exemplary composition combines the ingredients listed in Table 18, excluding the controlled release agent.
[0119] [Table 18]
[0120] The silicone base polymer used was SL 161 from Dow silicone. 7488, a silicone crosslinker provided by Dow, was added and mixed until uniform. SL 3000, a platinum solution, was used to give a ppm of platinum of 15 ppm by atomic weight of platinum. Finally, 0.25 parts by weight of trimethylolpropane triacrylate TMPTA was added to the mixture as a cure accelerator and mixed for 10 minutes.
[0121] Another exemplary composition combines the ingredients listed in Table 19, excluding the controlled release agent.
[0122] [Table 19]
[0123] The silicone base polymer used was SL 161 from Dow silicone. 7488, a silicone crosslinker provided by Dow, was added and mixed until uniform. SL 3000, a platinum solution, was used to give a ppm of platinum of 15 ppm by atomic weight of platinum. Finally, 0.25 parts by weight of propoxylated (3 mol) trimethylolpropane triacrylate TMPTA was added to the mixture as a cure accelerator and mixed for 10 minutes.
[0124] Another exemplary composition combines the ingredients listed in Table 20, excluding the controlled release agent.
[0125] [Table 20]
[0126] The silicone base polymer used was SL 161 from Dow silicone. 7488, a silicone crosslinker provided by Dow, was added and mixed until uniform. SL 3000, a platinum solution, was used to provide a ppm of platinum of 15 ppm by atomic weight of platinum. Finally, 0.25 parts by weight of polyethylene glycol 200 diacrylate (PEG200DA) was added to the mixture as a cure accelerator and mixed for 10 minutes.
[0127] Another exemplary composition combines the ingredients listed in Table 21, excluding the controlled release agent.
[0128] [Table 21]
[0129] The silicone base polymer used was SL 161 from Dow silicone. 7488, a silicone crosslinker provided by Dow, was added and mixed until uniform. SL 3000, a platinum solution, was used to give a ppm of platinum of 15 ppm by atomic weight of platinum. 0.25 parts by weight of 3-acryloxypropyltrimethoxysilane and 0.05 parts by weight of dodecyl vinyl ether as acrylate cure accelerators were added to the mixture and mixed for 10 minutes.
[0130] Using the control compositions of Tables 16 and 17, and compositions 1 through 5 shown in Tables 15 and 18 through 21, flexible liners were coated with a release layer and cured to form release liners.
[0131] 200 pounds of the control composition and compositions 1-4 were prepared and transferred to a container. The composition solutions in the container were coated as a release layer onto kraft paper using a 5-roll silicone coater. The coated paper was passed through three 20-foot ovens with a ramped temperature from 265°F to 330°F at a speed of 1850 feet / minute. This produces an exit web temperature of 310°F with an oven residence time of approximately 2 seconds for the purpose of curing the release layer composition into a release liner. The cured coated paper was re-moisturized with two steam foils to return the moisture level of the paper to pre-oven levels.
[0132] The release liner formed from each composition coating was used to form an adhesive article. The release liner was coated with a rubber-based hot melt adhesive material using a slot die coater. A heat transfer paper support was then laminated to the adhesive-coated construction surface to form an adhesive article.
[0133] In another example, 100 pounds of the control composition and compositions 1-5 were prepared and placed in a container. The composition solutions in the container were coated as a release layer onto kraft paper using a three-roll gravure silicone coating head. The coated paper was passed through three 20-foot ovens at two test speeds: 750 ft / min (for the control composition, and compositions 1, 3, and 4) and 1000 ft / min (for the control composition and compositions 1-5). The temperature of the coated paper after passing through the ovens was 290°F with oven residence times of 4.8 and 3.6 seconds for test speeds of 750 and 1000 ft / min, respectively, for the purpose of curing the release layer compositions into release liners. The release liners formed with each composition coating were used to form adhesive articles. The release layer side of the release liners was coated with an all-temperature acrylic emulsion adhesive and dried in an additional oven. A heat transfer paper support was then laminated to the adhesive-coated construction surface to form an adhesive article.
[0134] To test for silicone extractables, samples of each release liner containing the control composition and compositions 1-5 were peeled from the adhesive and substrate and the residual silicone coating remaining on the paper substrate was measured using an Oxford LabX 3500 instrument. Samples of known coating weight of the release liner were placed in 30 ml of MIBK or toluene and stirred for 30 minutes. Samples of known coating weight of the release liner were dried in a fume hood and the coating weight of each sample was remeasured. The difference between the original coating weight of the release liner and the peeled samples was compared to determine the amount of composition that had transferred from the coating of the release liner to the paper substrate of the adhesive article. The MIBK or toluene solutions were also tested for atomic absorption of silicone.
[0135] To test the 32 fpm peel force, cut a 16" x 2" piece in the complete laminate. Place the sample on an IMass Slip / Peel Tester TL-2300 and peel at 32 fpm. This same procedure is used to measure the 950 fpm peel force, but use an IMASS ZPE-1100W machine instead of the IMass Slip / Peel Tester TL-2300.
[0136] Silicone adhesion measurements: Samples are measured for silicone coverage using Oxford's LabX 3500, which is placed under a force of less than 10 pounds and rubbed over 2 feet along the felt surface at a speed of 24 fpm. The sample is then remeasured for coverage and the ratio of silicone coverage before and after abrasion is reported as a percentage of silicone adhesion.
[0137] Test data measured on adhesive articles including release layers formed with control Composition 1 and Compositions 1-4 in an oven at a speed of 1850 feet / minute are shown in Tables 22 and 23 below.
[0138] [Table 22]
[0139] [Table 23]
[0140] As shown in Tables 22 and 23, Compositions 1-4, which have half the platinum concentration (Composition 1) and one-quarter the platinum concentration (Compositions 2-4) of the control Composition 1, exhibited comparable and sometimes improved adhesion to paper substrates. The acrylate additives in Compositions 1-4 provide improved catalyst material savings, as 50%-75% less catalyst is required to achieve adequate adhesion to paper substrates.
[0141] Compositions 1-4 also exhibited sufficient percentages of silicone extractables, indicating that the compositions cured even with significantly reduced amounts of catalyst compared to Control Composition 1. As shown in Table 23, Compositions 1-4 containing 30 ppm or less of catalyst were measured to have 14% or less of silicone extractables. The sufficient cure of Compositions 1-4 was further supported by all compositions having more silicone adhesion than Control Composition 1. As shown in Table 23, Compositions 1-4 containing 30 ppm or less of catalyst were measured to have 60% or more, or 65% or more of silicone adhesion.
[0142] Test data measured for adhesive articles including a release layer formed in an oven at a speed of 750 feet / minute using the control composition 2, and compositions 1, 3, and 4 are shown in Tables 24 and 25 below.
[0143] [Table 24]
[0144] [Table 25]
[0145] As shown in Table 24, Compositions 1 and 3-4 showed improved adhesion to paper substrates over a range of peel speeds compared to the control Composition 2, which did not contain the acrylate additive. Thus, the acrylate additive contributes to enhanced adhesion performance without the need for an additional catalyst.
[0146] Compositions 1 and 3-4 also exhibited sufficient percentages of silicone extractables compared to Control Composition 2, indicating that the compositions cured even with a significantly reduced amount of catalyst. Control Composition 2 exhibited reduced cure, with 20.4% silicone extractables measured, compared to compositions with acrylate additives and the same or similar catalyst loadings. As shown in Table 25, Compositions 1 and 3-4 containing 30 ppm or less of catalyst were measured to have 12.4% or less silicone extractables, and Compositions 3 and 4 had 7% or less silicone extractables. Thus, Compositions 1 and 3-4 exhibited improved cure compared to Control Composition 2, which did not contain an acrylate additive. The sufficient cure of Compositions 1 and 3-4 was further supported by all compositions having more silicone fixation than Control Composition 2. As shown in Table 25, Compositions 1 and 3-4 containing 30 ppm or less of catalyst were measured to have 70% or more silicone fixation, or 80% or more silicone fixation.
[0147] Test data measured on adhesive articles including release layers formed with control Composition 2 and Compositions 1 to 5 in an oven at a speed of 1000 feet / minute are shown in Tables 26 and 27 below.
[0148] [Table 26]
[0149] [Table 27]
[0150] As shown in Table 26, Compositions 1-5 exhibited either equivalent or improved adhesion to paper substrates over a range of peel speeds compared to the control Composition 2, which did not contain the acrylate additive. Thus, the acrylate additive contributes to providing acceptable adhesion or enhanced adhesion performance without the need for an additional catalyst.
[0151] Compositions 1-5 also exhibited a sufficient percentage of silicone extractables compared to control composition 2, indicating that the compositions cured even with a significantly reduced amount of catalyst. Control composition 2 exhibited significantly reduced insufficient cure with 41.6% silicone extractables measured. As shown in Table 27, compositions 2-4 containing 15 ppm platinum catalyst were measured to have 14.8% or less silicone extractables, and compositions 2 and 3 had 13% or less silicone extractables. Thus, compositions 2-4 exhibited improved cure compared to control composition 2, which did not contain an acrylate additive. The sufficient cure of compositions 1-5 was further supported by all compositions having more silicone adhesion than control composition 2. As shown in Table 27, compositions 2 and 3 containing 15 ppm platinum catalyst were measured to have 70% or more silicone adhesion.
Claims
1. a) a substrate; b) an adhesive disposed on the substrate; and c) a release liner comprising a first surface; d) an adhesive article comprising a molding formed from the composition upon curing and disposed on the first surface of the release liner, The composition comprises: i) a silicone-based polymer; ii) an acrylate cure accelerator in a concentration in parts per million (pph) in the composition in the uncured state of 0.2 pph to 2 pph; iii) a catalyst present as less than or equal to 60 ppm of the total weight of said composition; Including, the molded article is obtained by exposing the composition to a temperature in the range of 70° C. to 140° C. for a period in the range of 1 second to 10 seconds, after which 90% or more of the composition is cured; The adhesive article has an elastic modulus (G') of 1 x 106 Pascals or more measured at a temperature of 120°C, and a loss factor (tan δ) of the composition after curing of less than 0.01 measured at a temperature of 120°C.
2. The adhesive article of claim 1 , wherein the silicone-based polymer is a vinyl-functional silicone-based polymer.
3. 10. The adhesive article of claim 1, wherein said silicone-based polymer is present between 50% and 95% by weight of the total weight of said composition.
4. The adhesive article of claim 1 , wherein the composition further comprises an O-vinyl ether compound.
5. 5. The adhesive article of claim 4, wherein the O-vinyl ether compound is selected from the group consisting of 1,4-cyclohexanedimethanol divinyl ether, butanediol divinyl ether, and dodecyl vinyl ether.
6. The adhesive article of claim 4, wherein the O-vinyl ether compound is present between 0.01% and 10% by weight of the total weight of the composition.
7. The adhesive article of claim 1 , wherein the composition further comprises a crosslinking agent comprising silicon hydride functional groups.
8. 10. The adhesive article of claim 1, wherein the composition further comprises a controlled release agent, the controlled release agent being present in an amount less than 50 weight percent of the total weight of the composition.
9. The adhesive article of claim 1 , wherein the catalyst comprises platinum.
10. 10. The adhesive article of claim 9, wherein the catalyst is present in a range between 10 ppm and 60 ppm of the total weight of the composition.
11. 10. The adhesive article of claim 9, wherein the catalyst is present at 35 ppm or less of the total weight of the composition.
12. The adhesive article of claim 1 , wherein the acrylate cure accelerator is the sole cure accelerator present in the composition.
13. 10. The adhesive article of claim 1, wherein the acrylate cure accelerator is present in an amount between 0.05% and 5% by weight, based on the total weight of the composition.
14. The adhesive article of claim 1 , wherein the release liner is selected from the group consisting of polymeric films, plastic films, and paper liners.
15. The adhesive article of claim 1 , wherein the molding is in contact with the adhesive.
16. The adhesive article of claim 1 , wherein the substrate is selected from the group consisting of polymeric films, paper, and combinations thereof.
17. The adhesive article of claim 1 , wherein the adhesive is a pressure sensitive adhesive.
Citation Information
Patent Citations
Peeling power-controlled solvent-free silicone peeling composition
JP1984084953A
Addition-curable silicone rubber composition
JP2000265067A
Silicone resin composition, and cured product thereof
JP2011148981A
Low-emission polyurethane foam made from isocyanate-reactive amine crystals
JP2017529437A